Pengaruh Orientasi Kewirausahaan, Inovasi, Kemampuan Menyusun Laporan Keuangan Dan Literasi Keuangan Terhadap Kinerja UKM - Arumega Zarefar; Vera Oktari; Atika Zarefar (Kajian Akuntansi, 2021)
To expand economic growth and development in Indonesia, small and medium enterprises (SMEs) have a very important role. The increasing number of SMEs has caused competition to become even more fierce. Not only that, the existence of SMEs also provides many benefits, one of which is by absorbing a lot of labor, so as to reduce the number of disruptions in Indonesia. Performance measurement is one way to assess the success of SMEs. By measuring performance, the company knows how much compensation will be given to its employees. The purpose of this study is to examine the effect of entrepreneurial orientation, innovation, the ability to prepare financial reports and financial literacy on the performance of SMEs. In this study, the data used are primary data with questionnaires as instruments. The population in this study is UKM in Kuantan Singingi, which amounts to 1,599 UKM. This study uses purposive sampling with a sample of 115 SMEs. Statistical test results show that entrepreneurial orientation, innovation and financial literacy have an influence on the performance of SMEs, while the ability to prepare financial reports has no effect on the performance of SMEs.